2021
DOI: 10.17762/turcomat.v12i2.2402
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey on Cryptography Evaluation in Mobile (MANETs)

Abstract: With the rapid development in network technology new network types based on wireless communication have emerged. A large family of wireless communication networks is the Mobile Ad hoc Networks (MANETs). While MANETs mobile devices should be able to connect with each other at any time and place, the vulnerabilities of MANET structure also introduce a wide range of attacks and present new challenges for the design of security mechanism ranging from developing and implementing lightweight cryptographic primitives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Efforts have been made to evaluate the algorithms' performances to determine their applicability to different information security requirements. Existing comparative studies have shown conflicting findings, and the selection of cryptographic algorithms used for comparison has been heavily weighted toward symmetric encryption techniques [8], [9]. Therefore, an attempt was made to strengthen some existing studies with the results obtained from the current study, and, in addition, both symmetric and asymmetric encryption/decryption algorithms were chosen for comparison in this study, as opposed to just symmetric algorithms in most previous studies.…”
Section: Introductionmentioning
confidence: 95%
“…Efforts have been made to evaluate the algorithms' performances to determine their applicability to different information security requirements. Existing comparative studies have shown conflicting findings, and the selection of cryptographic algorithms used for comparison has been heavily weighted toward symmetric encryption techniques [8], [9]. Therefore, an attempt was made to strengthen some existing studies with the results obtained from the current study, and, in addition, both symmetric and asymmetric encryption/decryption algorithms were chosen for comparison in this study, as opposed to just symmetric algorithms in most previous studies.…”
Section: Introductionmentioning
confidence: 95%